Heterotopic pregnancy in natural conception - M J Govindarajan; R Rajan (Wolters Kluwer Medknow Publications, 2008)
Heterotopic gestation, although common with assisted reproductive techniques, is very rare in natural conception. A high index of suspicion can help in timely diagnosis and appropriate intervention. We report a case of heterotopic pregnancy in a 22-year-old woman presented with hemoperitoneum from ruptured tubal pregnancy with live intrauterine gestation at 10 weeks of amenorrhea, diagnosed on ultrasound examination.